Associations of excessive internet use, sleep duration and physical activity with school absences : a cross-sectional, population-based study of adolescents in years 8 and 9 - Kosola, Silja; Kullberg, Marianne; Melander, Katja; Engblom, Janne; Ranta, Klaus; Alanko, Katarina (BMJ Publishing Group, 2025)
Background: Internet use has increased and sleep and physical activity (PA) have decreased in recent years among adolescents. Besides sleep and PA, another determinant of future health for adolescents is education. Our aim was to evaluate the associations of excessive internet use (EIU), short sleep duration and low PA with both unexcused absences and medical absences during lower secondary school.
Methods: The School Health Promotion study is a national survey of adolescents conducted biennially in Finland. We used data collected in 2019, when EIU was assessed for the first time. Cumulative odds ratio analysis was conducted with unexcused absences and medical absences as outcome variables. Besides EIU, sleep duration and PA, the associations of maternal education and parental relations were assessed.
Results: The mean age of the 86 270 participants was 15.3 years. Girls scored higher than boys on EIU. In all, 34.7% of participants slept less than 8 hours per night during the school week, and 34.3% reported low PA (ie, less than 3 days per week with minimum 1 hour of PA per day). EIU, short sleep and low PA were associated with both unexcused absences and medical absences from school. Longer sleep during weekends showed no association with absences, but good parental relations had the strongest protective association with both unexcused and medical absences.
Conclusions: EIU, short sleep duration and low PA were associated with both unexcused and medical absences from school. This has important implications for both the promotion of general health and the support offered to students with alarming school absences.